NATURE — THE PRICELESS WEALTH OF HUMANITY - Mahmudova Gulsoraxon (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article, written from the perspective of a 6th grade student from Uzbekistan, explores the profound importance of nature in our daily lives and for the future of humanity. It discusses how nature provides not only the physical necessities of life, but also brings peace, joy, and inspiration to the human soul. The article highlights the growing environmental challenges caused by human carelessness, and encourages every individual — especially young people — to take responsibility for protecting and preserving the natural world.